Home Truths?: Video Production and Domestic Life - David Buckingham, Rebekah Willett, and Maria Pini (Technologies of the Imagination, 2011)
Over the past decade, the video camera has become a commonplace household technology. With falling prices on compact and easy-to-use cameras, as well as mobile phones and digital still cameras with video recording capabilities, access to moving image production technology is becoming virtually universal. Home Truths? represents one of the few academic research studies exploring this everyday, popular use of video production technology, looking particularly at how families use and engage with the technology and how it fits into the routines of everyday life. The authors draw on interviews, observations, and the participants' videos themselves, seeking to paint a comprehensive picture of the role of video making in their everyday lives. While readers gain a sense of the individual characters involved in the project and the complexities and diversities of their lives, the analysis also raises a range of broader issues about the nature of learning and creativity, subjectivity and representation, and the ""domestication"" of technology-issues that are of interest to many in the fields of sociology and media/cultural studies.